Cardio-protective effects of phytosterol-enriched functional black tea in mild hypercholesterolemia subjects. (April 2017) - Orem, Asım; Alasalvar, Cesarettin; Vanizor Kural, Birgül; Yaman, Serap; Orem, Cihan; Karadag, Ayse; Pelvan, Ebru; Zawistowski, Jerzy
Highlights: Functional black tea (FBT) is an excellent beverage for delivering phytosterols. FBT significantly decreased the concentrations of total and LDL cholesterols. FBT would improve glucose metabolism, inflammatory, and endothelial factors. FBT had an additional health effects on some cardiovascular risk factors. Abstract: Hypercholesterolemia is a common condition in which the risk for the development of cardiovascular disease (CVD) is increased. Due to their hypocholesterolemic effects, phytosterols are considered to be effective in the prevention of CVD, particularly coronary heart disease. The aim of study was to investigate the cardio-protective effects of phytosterol-enriched instant black tea (functional black tea) in subjects with mild hypercholesterolemia. A randomized, double-blind, and placebo-controlled study was conducted on volunteer subjects aged 25–60 y with mild hypercholesterolemia [plasma total cholesterol concentrations 200–239 mg/dL (5.2–6.2 mmol/L)]. Subjects were randomly divided into placebo (PBO) ( n  = 33; M/F, 23/10), instant black tea (IBT) ( n  = 34; M/F, 25/9), and functional black tea (FBT) (2 g phytosterols/d) ( n  = 32; M/F, 24/8) groups and intervention period was conducted for 4 wk. Compared with baseline, consumption of FBT significantly decreased the concentrations of total cholesterol by 5.6% ( P  < 0.001), low-density lipoprotein (LDL) cholesterol by 8.7% ( P  < 0.001), apolipoprotein B ( P  < 0.05), and oxidative stress index ( P  < 0.05), while increasing the concentrations of adiponectin, total antioxidant status, and tissue-plasminogen activator ( P  < 0.05). FBT was superior to IBT in terms of cardiovascular risk biomarkers. The data indicate that consumption of newly developed FBT is an excellent beverage for delivering phytosterols and has several beneficial cardio-protective effects in subjects with mild hypercholesterolemia.